CONSIDERATIONS WITH REGARD TO THE USUFRUCT OVER THE RIGHT OF VOTE AS GUARANTY APPLIED IN THE BUSINESS ACTIVITY - Florin CONSTANTINESCU (Challenges of the Knowledge Society)
The aim of the present article is to scrutinize the usufruct over the right of vote related to a share as legal concept (from foregoing and current Romanian legislation and doctrine standpoint) and to highlight also the legal traits and the effective benefits provided as guaranty. To the same extent, the consolidation of the legal regime of this concept as guaranty is also the pursued objective. Although the usufruct over the right of vote has been not considered as a valid guaranty, the companies from Romania (mostly the banks) used this mechanism as guaranty within the (sophisticated) lending transactions. It is worthy to be mentioned that the right of vote may be related to a share belonging to a joint-stock company or to a social part belonging to a limited liability company. The main scope of such guaranty is to strengthen the creditor’s rights besides other established hard collaterals (mortgages over real estates, shares, receivables etc.). Thus, the creditor may influence the corporate will of a company (within the general shareholders meeting). Moreover, the guaranty has to be set up in the form of a notarized deed (authenticated by a Notary Public) aiming to be considered a writ of execution and to enable the creditor to commence the foreclosure if needed. Having in mind the above, this paper mainly regards: the content of the right of vote related to a share, security, social part, the applicability of the usufruct to the shares belonging to different companies (joint-stock companies listed or not listed to the Stock Exchange, other companies of capitals and persons), the relevant differences between the usufruct as dismemberment of the ownership right and the usufruct as guaranty, the significant aspects regarding the guaranty agreement, proposals to amend the legislation.